Effects of positive end-expiratory pressure and oxygen concentration on non-hypoxemic apnea time during face mask ventilation of anesthesia induction: A randomized controlled trial - Hao, Chunxiang; Ma, Xiaojing; Piao, Xiangmei; Fu, Yunke; Ma, Libin; Mi, Weidong; Berra, Lorenzo; Li, Changtian; Zhang, Changsheng (Frontiers in Physiology, 2023)
Background The optimal ventilatory strategy for the face mask ventilation during anesthesia induction is still unknow. Methods We evaluated the effect of 2 positive end-expiratory pressure (PEEP) levels and 2 oxygen concentration levels on non-hypoxemic apnea time during face mask ventilation of anesthesia induction. Sixty adult patients scheduled for elective surgery were enrolled in this study. The patients were randomized to receive anesthesia induction with 4 different ventilation strategy under volume-controlled ventilation. Patients assigned to the LOZP group received low fraction of inspiration O2 (FiO2=0.6) and 0 PEEP. Patients assigned to the LOHP group received low fraction of inspiration O2 (FiO2=0.6) and 6cmH2O PEEP. Patients assigned to the HOZP group received high fraction of inspiration O2 (FiO2=1.0) and 0 PEEP. Patients assigned to the HOHP group received high fraction of inspiration O2 (FiO2=1.0) and 6cmH2O PEEP. After 3 minutes of ventilation, the patient was intubated but disconnected from the breathing circuit. Ventilation was not initiated until the pulse oximetry dropped to 90%. The primary outcome was non-hypoxemic apnea time defined as the time from cessation of ventilation to a pulse oximeter reading of 90%. The secondary outcome was the PaO2/FiO2 ratio immediately after ventilation. Results The non-hypoxemic apnea time was significantly longer in the group of HOHP when compared to the other 3 groups (192 ± 70s, 221 ± 74 s, 284 ± 101s, and 353 ± 85s in the LOZP, LOHP, HOZP and HOHP group, respectively). The PaO2/FiO2 ratio immediately after ventilation was significantly higher in the group of LOHP when compared to the other 3 groups (LOZP 393 ± 130, LOHP 496 ± 97, HOZP 335 ± 58, HOHP 391 ± 50). When compared the PaO2/FiO2 ratio immediately after ventilation to its value before administration of anesthesia, the PaO2/FiO2 ratio in the group of LOHP was improved, the group LOZP and HOHP remained the same, while the group HOZP significantly decreased. Conclusion Application of PEEP and 100% of oxygen during face mask ventilation of induction could maximize the non-hypoxemic apnea time. However, the use of PEEP and 60% of oxygen during preoxygenation resulted in improved PaO2/FiO2 ratio.